2022
DOI: 10.1093/europace/euac130
|View full text |Cite
|
Sign up to set email alerts
|

The association of coagulation and atrial fibrillation: a systematic review and meta-analysis

Abstract: Aims While atrial fibrillation (AF) is suggested to induce a prothrombotic state, increasing thrombotic risk, it is also hypothesized that coagulation underlies AF onset. However, conclusive evidence is lacking. With this systematic review and meta-analysis, we aimed to summarize and combine the evidence on the associations between coagulation factors with AF in both longitudinal and cross-sectional studies. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 102 publications
1
9
1
Order By: Relevance
“…Fbg is an acute-phase reactant that responds to inflammatory processes or tissue damage and serves as a maker for prothrombotic state. Previous observational studies have demonstrated higher levels of Fbg in AF cases compared to healthy individuals [49] , which contradicts our finding. In observational studies, the levels of Fbg could be influenced by the confounding risk factors of AF and the coexistence of other cardiovascular diseases, potentially leading to an overestimation of Fbg concentration.…”
Section: Discussioncontrasting
confidence: 99%
“…Fbg is an acute-phase reactant that responds to inflammatory processes or tissue damage and serves as a maker for prothrombotic state. Previous observational studies have demonstrated higher levels of Fbg in AF cases compared to healthy individuals [49] , which contradicts our finding. In observational studies, the levels of Fbg could be influenced by the confounding risk factors of AF and the coexistence of other cardiovascular diseases, potentially leading to an overestimation of Fbg concentration.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown that patients with AF are also accompanied by altered PAI-1 levels [5]. A meta-analysis showed that elevated PAI-1 levels were associated with abnormal blood flow status in patients with AF [36]. In our study, D-Di and PAI-1 levels were significantly raised in NVAF patients combined with slow blood flow and were significantly and positively correlated with ADMA levels, which suggest that ADMA plays an important role in the regulation of abnormalities of the fibrinolytic system in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…FIB was also independently associated with 2-year all-cause and cardiac mortality in patients with CAD treated with PCI [ 11 ]. In a meta-analysis of coagulation and AF, there was a significant association between FIB levels and the incidence of AF; however, other cardiovascular risk factors, such as BMI or complications, weakened this association [ 54 ]. The association between FIB levels and NOAF incidence after PCI has not been studied.…”
Section: Discussionmentioning
confidence: 99%